Konsep Taksonomi Bloom dalam Desain Pembelajaran - Muhammad Afif Marta; Dimas Purnomo; Gusmameli Gusmameli (Pusat Riset dan Inovasi Nasional, 2025)
This paper discusses how Bloom's Taxonomy can be used in instructional design, as it serves as a framework for creating organized and effective learning objectives. Bloom's Taxonomy, created by Benjamin Bloom in 1956, divides academic objectives into six cognitive levels: knowledge, comprehension, application, analysis, synthesis, and evaluation. Bloom's Taxonomy 2.0, which places more emphasis on higher-order thinking processes and actions, has been adapted to the developments in education. By using this taxonomy in designing learning experiences, teachers can structure progressive instructional content that encompasses both the mastery of basic concepts and critical and creative thinking skills. Furthermore, this paper discusses how integrating Bloom's Taxonomy into the curriculum can enhance the quality of learning and encourage students to develop their thinking abilities. It also offers practical suggestions for educators on how they can create more engaging and meaningful learning experiences for their students. Bloom's Taxonomy has evolved into a highly valuable tool for supporting student learning at various educational levels.